NILAI-NILAI AKHLAK TASAWUF DALAM PENDIDIKAN ANAK PADA MASYARAKAT NTORI BIMA - Junaidin, Junaidin (Sulesana: Jurnal Wawasan Keislaman, 2019)
The study was descriptive qualitative research, aimed at identifying and analyzing the Sufism moral values in children’s education in Ntori Bima community. The child referred to in this study was a child who is the second offspring of his/her parents. The location of this research was in Ntori Village, Wawo District, Bima Regency, West Nusa Tenggara. Data sources were taken from the local community leaders regarded to understand and practice the moral values that can be detected by observing the scale of their spiritual attitudes. Observation, interview, and documentation were utilized in collecting the data. The researcher as the main instrument, observation guide, interview guide, and check list of documents as well as other supporting tools such as recorders, cameras and stationery were used as the research instruments. Data processing techniques employed were Miles and Hiberman techniques, starting from collecting, condensing, managing, and veriying the data. The quantitative data would be processed first with a percentage formula so that it could be e, while the qualitative data would be described. Triangulation technique was applied in testing the data validity. The results of the study revealed that the level of understanding on Sufism Moral values (fi tua) in the Ntori Bima community was still general and taught informally. While the forms of Sufism Moral values in children’s education in the Ntori Bima community were: (1) To’a ro nggahi rombo mantiri (obedient and honest), (2) maja labo dahu (embarrassed and afraid), (3) ngaji raso (purifying). These values shaped the character of the Ntori Bima people who were polite, shy, honest, trustworthy, and continue to be oriented towards kindness and sincerity. The implications of the study; (1) understanding Sufism moral values in children’s education by raising local values, (2) raising awareness to prioritize moral values in educating children, (3) being able to recognize, understand, and apply the moral values to be accustomed behavior, so that it could become an identity in the future.